2019
DOI: 10.1038/s41380-019-0432-2
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA regulation of persistent stress-enhanced memory

Abstract: Disruption of persistent, stress-associated memories is relevant for treating posttraumatic stress disorder (PTSD) and related syndromes, which develop in a subset of individuals following a traumatic event. We previously developed a stress-enhanced fear learning (SEFL) paradigm in inbred mice that produces PTSD-like characteristics in a subset of mice, including persistently enhanced memory and heightened cFos in the basolateral amygdala complex (BLC) with retrieval of the remote (30 day old) stress memory. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Consistent with this hypothesis, we recently demonstrated that exposure to a single acute stressor (120 min of restraint stress) induces a change in the molecular profile of the BLA, including differential expression of miRNAs an entire month after stress (Sillivan et al 2019b). Differential miRNA expression has also been reported in the serum of patients with PTSD (Zhou et al 2014;Martin et al 2017;Sillivan et al 2019a) and between rats selectively bred for high or low stress reactivity (Cohen et al 2017). The behavioral consequences of stress exposure have also been linked to miRNA function in the amygdala in several reports.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this hypothesis, we recently demonstrated that exposure to a single acute stressor (120 min of restraint stress) induces a change in the molecular profile of the BLA, including differential expression of miRNAs an entire month after stress (Sillivan et al 2019b). Differential miRNA expression has also been reported in the serum of patients with PTSD (Zhou et al 2014;Martin et al 2017;Sillivan et al 2019a) and between rats selectively bred for high or low stress reactivity (Cohen et al 2017). The behavioral consequences of stress exposure have also been linked to miRNA function in the amygdala in several reports.…”
supporting
confidence: 53%
“…miRNAs are small, approximately 22-24 nt long, noncoding RNAs that repress translation of target mRNAs (Filipowicz et al 2008;Gebert and MacRae 2019). miRNAs interact with multiple functional targets directly at the 3 ′ untranslated region of the target mRNA based on complimentary sequences and, therefore, have been hypothesized to support the complex patterns of gene regulation required to support not only the initial formation of longterm memory, but also the persistence of remote memory (Sillivan et al 2019a). In an early example linking miRNAs to learning and memory, knockdown of Dicer1, an enzyme required for mature miRNA processing, enhanced memory performance in the Morris Water Maze, trace FC, and contextual FC (Konopka et al 2010), confirming that miRNA function influences recent memory performance in several different types of tasks.…”
mentioning
confidence: 99%
“…miRNAs are single-stranded RNA molecules 18-25 nucleotides in length that regulate gene expression in many cellular processes (2,27). Although the protective role of miR-135b was previously reported in neurons (16,17), the expression pattern and specific role of miR-135b in AIS remain poorly understood. The present study demonstrated that miR-135b expression in the peripheral blood samples obtained from the IS group was higher compared with the healthy control group.…”
Section: Discussionmentioning
confidence: 98%
“…The neuroprotective role of miR-135b in SH-SY5Y cells and stress-enhanced memory has been previously demonstrated (16,17). In Parkinson's disease (PD), the protective role of miR-135b is achieved by targeting GSK-3β in SH-SY5Y cells intoxicated with 1-methyl-4-phenyl-pyridinium (16).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation